RESPONSIBILITIES OF A NOTARY AGAINTS AN AUTHENTIC DEED MADE BEFORE A NOTARY - Isma Widya Astuti B; Ma’ruf Hafidz; Sri Lestari Poernomo (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal